Neurorehabilitation and Physical Therapy - Nakano, Hideki (IntechOpen, 2023)
Neurorehabilitation (neuroscience-based rehabilitation) is a medical approach that utilizes the brain's plasticity to help patients recover from nervous system injury. Remarkable progress has been made in this field, thus attracting increased attention from the scientific community. The concept of neurorehabilitation is widely accepted in physical therapy, and evaluation and treatment based on this concept are currently being practiced. This book provides a comprehensive overview of neurorehabilitation with chapters on motor imagery, repetitive peripheral magnetic stimulation, virtual reality, neurofunctional interventional approaches, and much more.